The implementation of machine learning for classifying eligible students for a scholarship at Budidarma University - Elsya Sabrina Asmita Simorangkir; Nirwan Yakub; Amran Manalu; Tarmizi; Rian Farta Wijaya (Jurnal Mantik, 2022)
This study aimed to assist Universitas Budidarma in deciding the recipients of the Kartu Indonesia Pintar (KIP Kuliah) scholarship program. KIP Kuliah is managed by the Ministry of Education, Culture, Research, and Technology and aims to support academically talented students in furthering their education in higher education institutions. The study utilized a Decision Tree data mining classification method with the C4.5 and Cart algorithms. The results showed that if a potential student has the KIP Kuliah scholarship and a high test score, they will pass the verification and validation process. The accuracy of the C4.5 and Cart algorithms was 100% due to the use of matching data in the research. This study aims to make the selection process for KIP Kuliah recipients more efficient and targeted.